Fuzheng Jiedu granules against disease progression among high-risk adults with non-severe COVID-19: a multicenter retrospective cohort study - Hua, Qiaoli; Zheng, Danwen; Shui, Jingwei; Zhang, Tong; Qin, Shengle; Zhang, Hanhong; Yu, Bo; Wang, Longde; He, Hailang; Tan, Xinghua; Chen, Qiumin; Yang, Yang; et al. (Frontiers in Pharmacology, 2025)
BackgroundFuzheng Jiedu (FZJD) granules are widely used to treat coronavirus disease (COVID-19) since their market approval, but their clinical effectiveness remains uncertain. In this study, we aimed to evaluate the effectiveness of FZJD in reducing disease progression in high-risk adults with COVID-19.MethodsA multicenter, retrospective cohort study involving high-risk adults with non-severe COVID-19 was conducted in China from May 2021 to December 2022. The study was registered at the Chinese Clinical Trial Registry (ChiCTR2200058097; https://www.chictr.org.cn/bin/project/edit?pid=160010). Patients were categorized into two groups based on the administration of FZJD granules. The outcomes included disease progression, mechanical ventilation, intensive care unit (ICU) admission, and mortality. Propensity-score analyses and multivariable regression were performed to assess the effectiveness of FZJD granules. The effectiveness was further analyzed in different subgroups.ResultsA total of 1,644 patients (54.7% female patients; mean age, 62.3 years) were included, with 27.4% (451/1,644) receiving FZJD granules. After propensity score matching (PSM), 320 FZJD granule receivers and 320 non-receivers were matched. Those receiving FZJD granules were associated with lower risks of disease progression [adjusted odds ratio (OR), 0.21; 95% confidence interval (CI), 0.06–0.73], mechanical ventilation (OR, 0.15; 95% CI, 0.03–0.66), and ICU admission (OR, 0.08; 95% CI, 0.01–0.64) than those not receiving FZJD granules. The lower risk of disease progression in the FZJD group was confirmed by multivariable regression analysis and various propensity-score analyses. Furthermore, subgroup analyses demonstrated significant treatment benefits in patients with moderate COVID-19 at admission (no progression to severe disease) or in those who were not fully vaccinated (OR, 0.06; 95% CI, 0.01–0.50).ConclusionFZJD administration was significantly associated with a reduced risk of disease progression in high-risk adults with mild-to-moderate COVID-19.